2016
DOI: 10.1186/s12909-016-0617-1
|View full text |Cite
|
Sign up to set email alerts
|

Improving gross anatomy learning using reciprocal peer teaching

Abstract: BackgroundThe use of cadavers in human anatomy teaching requires adequate number of anatomy instructors who can provide close supervision of the students. Most medical schools are facing challenges of lack of trained individuals to teach anatomy. Innovative techniques are therefore needed to impart adequate and relevant anatomical knowledge and skills. This study was conducted in order to evaluate the traditional teaching method and reciprocal peer teaching (RPT) method during anatomy dissection.MethodsDebrief… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0
2

Year Published

2017
2017
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 51 publications
2
63
0
2
Order By: Relevance
“…Indeed, previous studies comparing the academic performance of students who received peer teaching to that of students who received no additional teaching found an improvement in the academic performance of students who participated (Benè and Bergus, ; Han et al, ). Furthermore, previous studies have demonstrated that students provide positive feedback about peer teaching (Goode et al, ; Furmedge et al, ; Agius et al, ), near‐peer teaching (Evans and Cuffe, ; Durán et al, ; Nelson et al, ; Rosenberg et al, ), and reciprocal peer‐teaching programs (Manyama et al, ). Moreover, beyond their gains in knowledge, students show improvement in understanding and retaining the material presented, improvement in study habits, more positive attitudes toward the subject, and independent self‐learning (Manyama et al, ; Bruno et al, ; Hanson et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, previous studies comparing the academic performance of students who received peer teaching to that of students who received no additional teaching found an improvement in the academic performance of students who participated (Benè and Bergus, ; Han et al, ). Furthermore, previous studies have demonstrated that students provide positive feedback about peer teaching (Goode et al, ; Furmedge et al, ; Agius et al, ), near‐peer teaching (Evans and Cuffe, ; Durán et al, ; Nelson et al, ; Rosenberg et al, ), and reciprocal peer‐teaching programs (Manyama et al, ). Moreover, beyond their gains in knowledge, students show improvement in understanding and retaining the material presented, improvement in study habits, more positive attitudes toward the subject, and independent self‐learning (Manyama et al, ; Bruno et al, ; Hanson et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Students who receive tutoring from peers also report improvements in understanding, interpersonal skills and study habits. (Lockspeiser et al, ; Manyama et al, )…”
Section: Introductionmentioning
confidence: 99%
“…To ensure continuity in the didactic activities, the same tutors are also involved in the exercitations on physical models. This method is indeed an effective approach by stimulating an active learning process, while also appreciating the three dimensions of anatomical structures (Youdas 2008;Hall 2013;Manyama 2016). Moreover, students learn through direct interactions from sharing similar discourse with tutors in a more informal and relaxed environment results (Glynn 2006;Field 2007).…”
Section: Design Coursementioning
confidence: 99%